MANAJEMEN MUTU DAN KEAMANAN PANGAN IKAN DEMERSAL BEKU DI PT. MARITIM TIMUR PERKASA, KOTA KUPANG, NUSA TENGGARA TIMUR - Diah Ayu Handini; Ainayah Naila Bajuri; Muhammad Afrisal; Moh. Ramadan Daud; Herning Pramudya; Luhur Bangun Widjaya (Universitas Mataram, 2026)
This study aims to describe the quality management system and food safety practices applied in the frozen demersal fish production process at PT Maritim Timur Perkasa. The research was conducted over a three-month period, from September to November 2025. A qualitative research method was employed through observation, interviews, and document review. The collected data were analyzed using descriptive analysis techniques. The results indicate that the processing stages of frozen demersal fish at PT Maritim Timur Perkasa generally comply with national standards; however, the gutting stage is not performed. Furthermore, the implementation of GMP and SSOP at PT Maritim Timur Perkasa has generally met the applicable standards, with 17 out of 18 GMP aspects being implemented, while all 8 SSOP aspects have been fully implemented. Nevertheless, several constraints related to quality management and food safety practices at PT Maritim Timur Perkasa still require improvement, including the absence of the gutting stage, some organoleptic parameters of raw materials being within a moderate range, incomplete product labeling, and limited specific laboratory testing for demersal fish.